Inter-Kingdom Modification of Metabolic Behavior: [GAR+] Prion Induction in Saccharomyces cerevisiae Mediated by Wine Ecosystem Bacteria - Ramakrishnan, Vidhya; Walker, Gordon A.; Fan, Qingwen; Ogawa, Minami; Luo, Yan; Luong, Peter; Joseph, C. M. Lucy; Bisson, Linda F. (Frontiers in Ecology and Evolution, 2016)
The yeast Saccharomyces cerevisiae has evolved to dominate grape juice fermentation. A suite of cellular properties, rapid nutrient depletion, production of inhibitory compounds and the metabolic narrowing of the niche, all enable a minor resident of the initial population to dramatically increase its relative biomass in the ecosystem. This dominance of the grape juice environment is fueled by a rapid launch of glycolysis and energy generation mediated by transport of hexoses and an efficient coupling of transport and catabolism. Fermentation occurs in the presence of molecular oxygen as the choice between respiratory or fermentative growth is regulated by the availability of sugar a phenomenon known as glucose or catabolite repression. Induction of the [GAR+] prion alters the expression of the major hexose transporter active under these conditions, Hxt3, reducing glycolytic capacity. Bacteria present in the grape juice ecosystem were able to induce the [GAR+] prion in wine strains of S. cerevisiae. This induction reduced fermentation capacity but did not block it entirely. However, dominance factors such as the rapid depletion of amino acids and other nitrogen sources from the environment were impeded enabling greater access to these substrates for the bacteria. Bacteria associated with arrested commercial wine fermentations were able to induce the prion state, and yeast cells isolated from arrested commercial fermentations were found to be [GAR+] thus confirming the ecological relevance of prion induction. Subsequent analyses demonstrated that the presence of environmental acetic acid could lead to [GAR+] induction in yeast strains under certain conditions. The induction of the prion enabled yeast growth on non-preferred substrates, oxidation and reduction products of glucose and fructose, present as a consequence of bacterial energy production. In native ecosystems prion induction never exceeded roughly 50-60% of the population of yeast cells suggesting that the population retains the capacity for maximal fermentation. Thus, the bacterial induction of the [GAR+] prion represents a novel environmental response: the query of the environment for the presence of competing organisms and the biological decision to temper glucose repression and dominance and enter a metabolic state enabling coexistence.